PERANCANGAN SISTEM INFORMASI WEBSITE PADA SMA ISLAM TERPADU INSAN HARAPAN KARAWANG - Asiyah; Imas (Program Studi Teknik Informatika Universitas Nusa Putra, 2024)
Designing a school website information system is generally carried out to provide information that is more easily accessible and managed to students, teachers, parents and the general public. With the school website, information about school activities and other information can be accessed easily and quickly. Apart from that, the school website can also be used as a promotional tool for the school. By displaying information about the school profile, educational programs, student achievements and other advantages, the school website can be an effective medium for introducing the school to prospective students and parents. This research is to design a school information system at SMAIT INSAN HARAPAN KARAWANG to integrate school information so that it can improve the quality of education so that it is better known by the general public and is expected to make it easier to access information. This system uses the PHP and MySql programming languages as database servers and tools using flow charts, ERP. Development of the school website information system uses the waterfall development methodology. With a good school website information system, it is hoped that it can help improve the quality of education and the effectiveness of communication between schools, students, parents and the general public. It is hoped that this system can be developed and carried out regular maintenance so that it can be used for a long time.